The problems of determining the competence of the subjects of the Russian Federation in the field of family protection - S. Narutto (Правоприменение, 2017)
УДК 342This article is dedicated to one of the problematic issues of Russian federalism – the definition of the competence of subjects of the Russian Federation in the social sphere related to the protection of the family.Results. It examines in detail the legislative powers of the regions on the subjects of joint conducting with the Russian Federation providing the state guarantee protection and family support. The author addresses to the analysis of the provisions of the Constitution of the Russian Federation, charters and constitutions of subjects of Federation, the current Federal and regional laws, decisions of the constitutional (Charter) courts of constituent entities of the Russian Federation, devoted to family relations. Attention is drawn to the variety of regional sources, including the codified legislative acts.Special attention is paid to the analysis of additional safeguards for the support of family, motherhood, fatherhood and childhood, established by the Federation.Among the measures of social support of families with children are allocated 1) a single, monthly and annual cash payments; 2) provide in-kind assistance; 3) provision of benefits; 4) organization of social services. Analyzed regional laws establishing benefits for newborn children measures of social support of large families and young families, specific support to traveller families, as well as laws about the rights of children, safeguards the rights of children-orphans and children left without parental care, about public tutors of minors, commissioners for the rights of the child.Conclusion. Geographic, geopolitical, economic, political, ethnic and other peculiarities of the Russian regions attract particular creation and activities of their government, including lawmaking. The necessity of preserving the rights of subjects of the Russian Federation on advancing the legal regulation in subjects of joint conducting.Criticized Federal legislation, annually changing the list of powers of authorities of subjects of the Russian Federation including those provided by protection and family support. The main problem of realization of the competence of subjects of the Russian Federation in the field of protection of the family the author is seen in the shortcomings of their legal definition, in securing for the subjects of authority without adequate financial support.